Evaluation of the main MPPT techniques for photovoltaic applications - De Brito, Moacyr Aureliano Gomes [UNESP]; Galotto, Luigi; Sampaio, Leonardo Poltronieri [UNESP]; De Azevedo Melo, Guilherme [UNESP]; Canesin, Carlos Alberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper presents evaluations among the most usual maximum power point tracking (MPPT) techniques, doing meaningful comparisons with respect to the amount of energy extracted from the photovoltaic (PV) panel [tracking factor (TF)] in relation to the available power, PV voltage ripple, dynamic response, and use of sensors. Using MatLab/Simulink and dSPACE platforms, a digitally controlled boost dc-dc converter was implemented and connected to an Agilent Solar Array E4350B simulator in order to verify the analytical procedures. The main experimental results are presented for conventional MPPT algorithms and improved MPPT algorithms named IC based on proportional-integral (PI) and perturb and observe based on PI. Moreover, the dynamic response and the TF are also evaluated using a user-friendly interface, which is capable of online program power profiles and computes the TF. Finally, a typical daily insulation is used in order to verify the experimental results for the main PV MPPT methods. © 2012 IEEE.
Keywords: Photovoltaic (PV) energy; PV maximum power point (MPP) tracker (MPPT) algorithms; PV power profile; PV tracking factor (TF); Agilent; Analytical procedure; Boost DC-DC converter; D-space; MATLAB /simulink; Maximum power point; Maximum Power Point Tracking; Online programs; Perturb and observe; Photovoltaic; Photovoltaic applications; Photovoltaic panels; Power profile; Proportional-integral; Solar arrays; User friendly interface; Voltage ripples; DC-DC converters; Dynamic response; Algorithms